An Evaluation of the Long-term Worldwide Availability and Market Value of Zirconium and Hafnium in Relationship to Future Demands Utilizing the WORLD7 Model - Harald Ulrik Sverdrup; Antoniy Elias Sverdrup (Science and Technology - Recent Updates and Future Prospects Vol. 1, 2024)
The long-term supply, price dynamics and recycling of zirconium and hafnium were assessed with the WORLD7 model. The total potential resources have been estimated at least 640-800 million tons of zirconium and 16-22 million tons of hafnium, it is estimated that about 320 million tons of zirconium is extractable. The WORLD7 model simulations show that the supply of zirconium will be in soft scarcity, caused by expensive manufacture and limited production capacity. Hafnium is in demand for superalloys in excess of the present production capacity (90 tons per year in 2022), rather than the size of the hafnium resource (20 million tons). The degree of recycling for zirconium and hafnium is at present far too low. The production and supply of these metals are predicted to peak around 2100, dependent on when the global population peaks and demand peaks. The zirconium resource will be sufficient for metal production for business-as-usual. For increased demand, scarcity may arise from delays in the adaptation of production capacity for zirconium and hafnium. The long-term sustainable extraction of zirconium is equivalent to a total extraction of 210,000 ton/yr of zirconium element for the supply of oxide and metal supply, far below the present extraction. Zirconium extraction would be sustainable at a recycling rate of 86%. For hafnium, the sustainable extraction is 2.5% of the total zirconium amount, or 5.2 tons/yr. Thus, hafnium extraction is not long-term sustainable, unless the recycling rate is better than 94%.